Masculinities and third gender: the origins and nature of an institutionalized gender otherness in the ancient Near East - Peled, Ilan (Alter Orient und Altes Testament, 2016)
The aim of this book is to track a distinct human phenomenon in the history of the ancient Near East: persons who were born males, but under various social and historical circumstances their masculine identity was considered to be ambiguous. On the basis of this, these persons can be classified as belonging to a third gender. They bore specific titles, and were engaged in cult or palace administration. The contexts of their documentation occasionally depict them as possessing or exhibiting traits that were uncharacteristic of the standard social expectations of men in Mesopotamia. 0The present research demonstrated that this human phenomenon of a third gender in the ancient Near East involved mainly the matter of social definitions. Social identity is defined by its limitations: where it begins and ends, and what exists beyond it. The strange, the extreme and the bizarre signify what common, hegemonic, people are not, and therefore mark who common, hegemonic, people actually are. These boundaries are constructed by using social mechanisms of norms and prohibitions. In this sense, the third gender figures were socially constructed, and served social needs of defining norms of conformity